(untitled) (Phenomenology, Humanities and Sciences, 2025)
Maurice Merleau-Ponty’s posthumously published book, The Visible and the Invisible, is one of most cited of all his works. The book was edited by Claude Lefort in 1964. It is clear that Merleau-Ponty was engaged in an important new work that was cut short by his untimely death in 1961. The published text of The Visible and the Invisible is comprised of a few drafts of chapters and many pages of enigmatic working notes. Despite its incomplete status, it is often heralded as the culmination of Merleau-Ponty’s thought. Some see it as the triumphant achievement of his lifelong phenomenological project, while others maintain view it as the inauguration of an important departure therefrom. Rather than endorsing any particular interpretation, here I want to call attention to the important role Lefort played in the presentation of Merleau-Ponty’s posthumous work. If not for Lefort’s effort in editing and publishing some of Merleau-Ponty’s final reflections, contemporary readers would have had no access to Merleau-Ponty’s exciting nascent project. However, based upon several years of archival research with Merleau-Ponty’s unpublished notes and manuscripts, I argue that Lefort’s presentation of Merleau-Ponty’s final works is selective and tendentious.